2016
DOI: 10.1007/978-1-4939-6412-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up of Protein Purification: Downstream Processing Issues

Abstract: Separation science continues to occupy the central position in the overall strategy for the downstream processing and purification of therapeutic protein products for human use. Increasing product titers from mammalian cell culture and new emerging classes of biopharmaceuticals has presented a challenge to the industry to identify ways of improving the robustness and economics of chromatography processes. In commercial manufacturing, there is always a need to increase the scale of the chromatography operations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Thus, downstream processing has become a bottleneck in biotherapeutic production 29 . Efforts to alleviate this have mostly focused on innovations in process design to improve downstream processing capacity, speed, and economics 30,31 . It has also been suggested that cell line engineering could be used to reduce or remove problematic HCPs, lessening the need for additional purification steps 6,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, downstream processing has become a bottleneck in biotherapeutic production 29 . Efforts to alleviate this have mostly focused on innovations in process design to improve downstream processing capacity, speed, and economics 30,31 . It has also been suggested that cell line engineering could be used to reduce or remove problematic HCPs, lessening the need for additional purification steps 6,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Although our maximum protein load amounts were chosen to allow for maximum resolution, one also needs to consider that our method is envisioned to be used as a secondary purification or polishing step where dynamic binding capacity is a secondary consideration. 40 This combination of IEX and linear pH gradient elution can thus be used where the lower resolution salt gradients result in insufficient separation of heterodimer from homodimers and other impurities. Although we demonstrated here the application of our method for the purification of common LC bispecifics, it can also be used for the purification of other bispecific formats as long as the impurities to be removed have a sufficiently different apparent pI.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the DSP is determined by the required purity of the product, which depends on the application and authorization. Performance criteria to be considered in developing an optimized purification process are speed, recovery, capacity, and resolution (Milne, 2017). A process developed in a laboratory (e.g., in 0.5 to 10 L fermenters) must be translated into a full manufacturing scale process (e.g., 20.000 to 2.000.000 L fermenters; Crater and Lievense, 2018).…”
Section: Purification Processes For Fermentation Products: What Is Fe...mentioning
confidence: 99%